Transplacental antibodies. Part III: Maternal antibodies against polioviruses, M. parotitidis and M. parainfluenzae - Čelko, Alexander Martin; Buriánová-Vysoká, Běla; Fedová, Dagmar; Koza, J; Zikmundová, V; Zikmund, Vladimír; Stríbrný, J (Journal of hygiene, epidemiology, microbiology and immunology, 1985)
In 1981 we examined 247 sera for the presence of antibodies against all three types of poliovirus and 253 sera for antibodies against M. parotitidis and three types of M. parainfluenzae viruses. The sera were obtained from the cord blood of mothers between 15 and 34 years of age. All mothers were divided into four age groups, each with primipara and multipara subgroups. The rate of seropositivity for type 1 and type 2 poliovirus-specific antibody was in all age groups higher than 90%, the overall seropositivity rate for type 3 poliovirus antibody was 83.6%, with 73.1% as the lowest rate for age group of youngest mothers. Significant seropositivity variations between the primipara and multipara subgroups were recorded only for type 3 antibody in the two age groups of oldest mothers (25-29 and 30-34 years). This is consistent with the assumed booster effect of Sabin vaccine strains on mothers of families with more than one child. Antibodies specific to mumps virus were present in the cord blood of 78.6% of all mothers and the rates of seropositivity were found to rise with the increasing age. Seropositivity for M. parainfluenzae type 1-specific antibody was demonstrated in 95.8%, for type 2-specific antibody in 98.9% and for type 3-specific antibody in 100% of mothers, which is suggestive of high herd immunity levels in the population.
Keywords: věkové faktory; placenta; Pregnancy; lidé; ženské pohlaví; Paramyxoviridae Infections; Poliomyelitis; Maternal-Fetal Exchange; maternofetální výměna látek; mladiství; Adolescent; Female; Mumps; Fetal Blood; Adult; Poliovirus; Mumps virus; Antibodies, Viral; fetální krev; protilátky virové; infekce viry z čeledi Paramyxoviridae; příušnice; Humans; poliomyelitida; Poliovirus Vaccine, Oral; poliovirová vakcína orální; dospělí; virus příušnic; Respirovirus; těhotenství; Age Factors; Placenta